2017
DOI: 10.1017/s1047951117002311
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen and indomethacin differentially regulate vascular endothelial growth factor and its receptors in ductus arteriosus endothelial cells

Abstract: Our results indicate differential effects of ibuprofen and indomethacin on the expression levels of the vascular endothelial growth factor system in ductus arteriosus endothelial cells. In addition, vessel-specific differences between ductal and aortic endothelial cells were found. Further in vivo studies are needed to elucidate the biological significance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The choice of indomethacin or ibuprofen to treat PDA is highly variable among neonatologists and is often influenced by non-clinical factors such as difficulties with drug supply (10)(11)(12). Nevertheless, there are pharmacokinetic, pharmacodynamic and pharmacogenetic differences between ibuprofen and indomethacin that may account for a different response in particular subgroups of preterm infants (72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of indomethacin or ibuprofen to treat PDA is highly variable among neonatologists and is often influenced by non-clinical factors such as difficulties with drug supply (10)(11)(12). Nevertheless, there are pharmacokinetic, pharmacodynamic and pharmacogenetic differences between ibuprofen and indomethacin that may account for a different response in particular subgroups of preterm infants (72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…indomethacin did not affect the expression levels of the vascular endothelial growth factor system in ductus arteriosus endothelial cells. 7 Several authors investigated vascular endothelial growth factor polymorphisms and their potential association with neonatal morbidities such as bronchopulmonary dysplasia, [10][11][12] retinopathy of prematurity, 8,9 and intraventricular haemorrhage 16 in preterm infants. However, the role of the vascular endothelial growth factor polymorphism rs2010963 on patent ductus arteriosus incidence and treatment success rates has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 We have recently shown that ibuprofen and indomethacin differentially regulate vascular endothelial growth factor and its receptors in primary endothelial cells of the rat ductus arteriosus. 7 In addition, several studies discussed vascular endothelial growth factor polymorphisms as potential risk factors for several diseases in neonates, including retinopathy of prematurity 8,9 and bronchopulmonary dysplasia. [10][11][12] The aim of the current study was to investigate the incidence of the vascular endothelial growth factor polymorphism rs2010963 status in a large cohort of preterm infants with and without patent ductus arteriosus and its potential association with cyclooxygenase inhibitor treatment success rates.…”
mentioning
confidence: 99%